Assessment of Concentration and the Annual Effective Dose of Radon Gas in Imam Hospital Indoor Air - Kobra Verijkazemi; Nabiollah Mansouri; Faramarz Moattar; Mostafa Khezri (Mazandaran University of Medical Sciences, 2016)
Introduction and purpose: Exposure to natural sources of radiation, especially radon and its short-term products, is an important issue around the world. Radon exposure causes lung cancer in humans. Therefore, the aim of this study was to measure the concentration of radon gas and its annual effective dose in Imam Hospital of Tehran, Iran and to compare its concentrations with the recommended standards. Methods: Radon levels and meteorological parameters (temperature, pressure, and moisture) were measured in different levels and in four seasons, using Radstar and Lutron Electronic devices, respectively, during June 2014-June 2015. The collected data were analyzed through SPSS 18. Annual effective dose was calculated, using the equation for annual effective dose introduced by Scientific Committee of the United Nations. Results: The highest concentration of radon and annual effective dose were observed in the winter, which were 82/15 Bq/m3 and0/48 ms/y, respectively. Furthermore, concerning the various levels, the highest concentration was observed in the lowest level (56/1 Bq/m3).Conclusion: The results of the current study demonstrated that radon concentration was lower than the standards set by Environmental Protection Agency and World Health Organization. Regarding this, there are not concerns about the possible dangers of radon gas activities for the personnel and patients of the hospital.